The The Relationship between Home Environmental Sanitation and ISPA Incidence in Toddlers in Kaleroang Village, South Bungku District, Morowali Regency: Environmental Sanitation and ISPA - Muhammad Ikhsan Akbar; Ali, Leniarti; Rachman, Wa Ode Nova Noviyanti; Mulyani, Sri; Sari, Triyah Indah (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Acute Respiratory Infection (ARI) is the main cause of death in toddlers which is still a health problem in Indonesia, especially in the Kaleroang Health Center UPT work area which is increasing every year. Namely, in 2020 the prevalence of ARI cases is as much as (21.7%) in 2021 as many as (28.5%) and in 2022 the prevalence will increase (28.9%). The purpose of this study was to determine the relationship between home environmental sanitation and the incidence of ARI in toddlers in Kaleroang Village, South Bungku District, Morowali Regency. Methods: This type of research is a quantitative study with a cross sectional study design. The population in this study were all mothers who had toddlers in Kaleroang Village, namely 106 people, the total sample was 84 people who were taken by random sampling . Retrieval of data using observation sheets and questionnaires. Data were analyzed statistically using the Chi-Square test. Results: The results of this study indicate that there is a relationship between home ventilation and the incidence of ARI in toddlers with a value of X2 counts (5.841) > X2 tables (3.841), house occupancy density2 counts (7.171) > X2 tables (3.841), members smoking habits family X2 counts (4,701) > X2 tables (3,841), use of mosquito coils X2 counts (10,903) > X2 tables (3,841), and immunization status X2 counts (5,409) > X2 tables (3,841). Conclusions: it can be concluded that house ventilation, house occupancy density, smoking habits of family members, use of mosquito coils, and immunization status are related to the incidence of ARI in toddlers in Kaleroang Village. It is suggested to the UPT Kaleroang Health Center to further increase education related to the risk of ARI transmission based on the environment.